Just say no to Microsoft : how to ditch Microsoft and why it's not as hard as you think - Bove, Tony, 1955- (No Starch Press, 2005)
Just Say No to Microsoft begins by tracing Microsoft's rise from tiny software startup to monopolistic juggernaut and explains how the company's practices over the years have discouraged innovation, stunted competition, and helped foster an environment ripe for viruses, bugs, and hackers. Readers learn how they can dump Microsoft products - even the Windows operating system - and continue to be productive. The book also shows how to work successfully and seamlessly with computers and people who are still hooked on Microsoft software. Includes full explanations of alternate operating systems, s.